Henna-induced acute hemolysis in an elderly woman: a rare case report from the Maldives - Rajib Kumar Dey; Ali Abdulla Latheef; Hisham Ahmed Imad; Moosa Murad (SpringerOpen, 2022)
Abstract Background Glucose-6-phosphate dehydrogenase enzyme deficiency is the most common enzymopathy in the world with a high prevalence in people of sub-Saharan Africa, Asia, and Mediterranean region. Being an X-linked recessive disorder, majority of the patients are males, and women get affected only if they are homozygous or double heterozygous for G6PD mutants. These patients are usually asymptomatic and present with an acute episode of hemolytic anemia when exposed to certain medications, chemicals, infections, fava beans, or any oxidative stress. Case presentation Here, we report a rare case of acute hemolytic anemia in an elderly woman following exposure to henna. On evaluation, she was found to be G6PD-deficient. We postulate that with increasing age, there is an increase in the amount of skewing about 70-90% in women above 70 years old which may lead to hemolysis in G6PD-deficient patients. Conclusion We advise all healthcare workers to keep a close eye and screen for G6PD deficiency in all elderly women presenting with acute hemolytic anemia.